NEED ANALYSIS TO DEVELOP FUNDAMENTAL MODEL OF MOVEMENT BASED ON TEAM GAMES TOURNAMENT (TGT) FOR STUDENTS IN THE ELEMENTARY SCHOOL - fahrudin; Moch. Asmawi; Firmansyah Dlis; Resty Gustiawati (Program Pascasarjana Universitas Negeri Jakarta, 2020)
The problem for students in the elementary school is often undergo to unconfident to learn movement, irresponsible in a group, unstable in awakening positive motivation to dare to take action. These are needed to help students in learning habituation especially in psychical education. Movement learning and teaching through of this game competition has a positive impact for leaning, so that it is helping students to foster self-assured and self-esteem. The goal of this research is to recognize the level of developing movement model based on team games tournament to students in the elementary school level. This paper applied of Quantitative approach with embracing survey method to scrutinize need analysis for students in the elementary school about the progression of fundamental movement which is adapted to characteristics of the students’ age among 4 to 12 years old. This is a pre-eleminary research to do seminar project in the future with the topics based on team games tournament (TGT). The population of this research involved 30 elementary school in the Rengasdengklok as the sub-districts. Meanwhile, the sample of this research is around 10 sport science teachers in the elementary school in the sub-district Rengasdengklok. For sharping the data, the researchers used incidental technique to examine the sample. Based on the need analysis, there are 70 % physical education in the elementary school said that they need to develop a model as fundamental movement based on TGT and the aptitude to develop the basic movement to acquire fundamental movement to students. Therefore, the researchers concluded that the teacher in the physical science education in the elementary school develop fundamental basic movement based on students in the elementary school.